Valuating agricultural water use and ecological services in agrarian economies: evidences from eastern India - Xenarios, Stefanos; Amarasinghe, Upali A.; Sharma, Bharat R. (2011)
Agricultural water use in agrarian economies is often state subsidized for the enhancement of agricultural productivity while poverty alleviation is also targeted. The Indian agricultural dependent states offer representative examples of undervalued irrigation services mainly sourced by canal networks. However, the current inefficient operation of canal irrigation systems diverts water demand to private initiatives by significantly increasing economic value of agricultural water. The additional recent acknowledgement of economic value encompassed in supportive ecological services enhances the request for reevaluation of agricultural water. The paper attempts to assess the value of irrigation and related ecological services in representative backward clusters of Bihar state in Eastern India. The effects on different landholding groups are analyzed by giving particular emphasis to marginal landholders.